2019
DOI: 10.1039/c9dt90027f
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Ferrocene-appended pharmacophores: an exciting approach for modulating the biological potential of organic scaffolds

Abstract: Correction for ‘Ferrocene-appended pharmacophores: an exciting approach for modulating the biological potential of organic scaffolds’ by Amandeep Singh et al., Dalton Trans., 2019, DOI: 10.1039/c8dt03440k.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In this work, the ferrocene molecule, one active compound with low levels of in vivo toxicity, was coupled in N-terminus of the peptide RP1 aiming to obtain a more active compound (Fc-RP1). Previous studies showed that compounds conjugated with organometallics, like ferrocene, has great biological potential [38,40,52,[70][71][72][73].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…In this work, the ferrocene molecule, one active compound with low levels of in vivo toxicity, was coupled in N-terminus of the peptide RP1 aiming to obtain a more active compound (Fc-RP1). Previous studies showed that compounds conjugated with organometallics, like ferrocene, has great biological potential [38,40,52,[70][71][72][73].…”
Section: Plos Onementioning
confidence: 99%
“…However, the Fc-RP1 conjugated showed higher toxicity (17.3 μmol L -1 ) when in contact with macrophage as compared with the same tests for RP1 peptide and ferrocene carboxylic acid molecule (>100 μmol L -1 ). It is well-known that bioconjugates containing organometallic compounds such as the ferrocene have great biological potential [40,64,71,73]. It is also assumed that this compound acts in the generation of reactive oxygen species.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The coupling constant J is reported in hertz (Hz). 1 H-and 13 C-NMR peaks were assigned based on the combined analysis of a series of 1 H-1 H (COSY) and 1 H-13 C (HSQC, HMBC) correlation spectra.…”
Section: Generalmentioning
confidence: 99%
“…The use of ferrocene building blocks in medicinal chemistry is an intriguing research area. Apart from its anticancer, antibacterial, antifungal, and antiparasitic potential [1], the ferrocenyl moiety has been increasingly used in drug design [2]. In particular, the bioisosteric replacement of a phenyl ring or heteroaromatic with the ferrocenyl group can lead to compounds with enhanced potency and/or selectivity, compared with the parent, purely organic molecule [3].…”
Section: Introductionmentioning
confidence: 99%